LXX Isaiah 24:1-26:6 as interpretation and translation : a methodological discussion - Cunha, Wilson de Angelo (Septuagint and cognate studies series ;, 2014)
This work demonstrates that LXX Isa 24:126:6 can be seen as a coherent ideological composition differing greatly from MT Isa 24:126:6 and concludes that the scribe or translators interpretation of his Hebrew Vorlage preceded and shaped his translation into Greek.